Social Selling - A Study of the Status Quo in Germany - Marco Schmäh; Martin Meyer-Gossner; Patrick Schilling; Sebastian Gruhn (Marketing Review St.Gallen, 2017)
In the lights of an increasing digitalization of companies, the sales process might experience changes in the usage and the influence of digital tools. In order to examine the status quo of German companies in this regard, a study was conducted between 235 participants. The results of this study will be outlined in the article at hand.
Keywords: 650